The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.enpol.2018.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of innovation policy criteria to the development of local renewable energy systems

Abstract: Renewable energy systems (RES) are becoming a strong component of local sustainable innovation strategies. Using a policy mix perspective, this paper investigates innovation policy criteria from municipalities' locational factors, cooperation activities among stakeholders, and local knowledge about RES as antecedents to see how they leverage the development of local RES. We studied these antecedents at a local level by analyzing a sample of 727 middle and large German municipalities using instrumental variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 97 publications
0
27
0
5
Order By: Relevance
“…They have shown that the development of community energy has been substantially shaped by the national regulatory frameworks and depends particularly on whether and how feed-in tariffs for renewable energies have been implemented [7,13]. Other authors have emphasized the need for local acceptance and support for the development of renewable energy projects and thus the importance of local actors for community energy [18][19][20]. Municipalities are such actors.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that the development of community energy has been substantially shaped by the national regulatory frameworks and depends particularly on whether and how feed-in tariffs for renewable energies have been implemented [7,13]. Other authors have emphasized the need for local acceptance and support for the development of renewable energy projects and thus the importance of local actors for community energy [18][19][20]. Municipalities are such actors.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy systems are becoming a strong element of local sustainable development strategies. The answer to the question remains whether direct financial support for renewable energy systems has an impact on the increase in the use of renewable energy [45]. It seems that in Polish conditions, with a less prosperous society and a not very well-developed renewable energy sector, direct support may, however, be the main incentive to invest in renewable energy.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, three recurring themes have been identified in the selected sample, specifically collaboration via the 'Triple Helix' (e.g. Barrie et al, 2017;Frank et al, 2018), the deliberate shaping of the conditions for interaction (e.g. Elsner, 2004) and navigating through public concerns (e.g.…”
Section: State-centric Approachmentioning
confidence: 99%